Participatory Approaches in Formulation of Public Policy at Nagari Governance Level - Suci Asfarina; Aldri Frinaldi (Jurnal Teori dan Riset Administrasi Publik, 2019)
Nagari governance is the smallest governmental organizer in Indonesia. Nationally,this governance is known as the Desa (village) governance. With the presence of regional autonomy by which region may manage its own governance in accordance with its local wisdom, West Sumatra uses the name ‘Nagari’ to replace the name. Between the Nagari governance and Desa governance, administratively it makes no difference, still the same rights and obligations, binding rules are the same. The difference is, in the enforcement of Nagari governance, there are customary elements in every aspect of its enforcement. Similarly, in public policy-making (policy formulation), the customary elements also include in the policy formulation process. In the case of this rulemaking, West Sumatra involves several actors, they are Nagari Trustees and their staffs, BPRN (people’s representative body of the village) and KAN (customary villagey density). But what happens is a lot of village governments just make regulations based on routine activities, while the rules that are derived from the aspirations of the people can be said to be absent in the last period of 1 year. As what happened in Salimpaung village, Salimpaungsubdistrict, that no regulations that appear in accordance with the needs of society. During the time, villagey regulations were made because of routine activities such as budgeting, etc. This phenomenon attracted the researchers' attention because the government also has the authority to make regulations in accordance with the needs of society.